Investigation of the expression levels of miR-21, miR-132, miR-29a, miR-204, and miR-138 in patient’s plasma with primary OSCCs: Expression levels of miRs in OSCC plasma - Tahmasebi, Elahe; Kamali Hakim, Lotfollah; Yazdanian, Mohsen; Asadi, Amirali; Garajei, Ata; Nezaminia, Sayna; Arabi Daredor, Amir Mohammad; Khafaei, Mostafa; Kahrizi, Soheil; Tavallaie, Mahmood (Cellular and Molecular Biology, 2022)
This is the eighth most malignant tumor in the world, causing the highest incidence and malignancy rate of all cancers in the mouth and maxillofacial region. In cells, miRNAs regulate development, differentiation, proliferation, and differentiation, and miRNA expression is a better indicator of physiological status than DNA expression. miR-21, miR-132, miR-29a, miR-204, and miR-138 levels were measured in plasma from patients with primary OSCC and healthy controls. A Real Time-PCR technique was used to measure miR-21, miR-132, miR-29a, miR-29a, and miR-204 expression levels in plasma from 38 healthy and 38 people with primary OSCC. A standard distribution test and a CT unit were used to confirm the quantitative data on miRNA expression. Gene expression levels were compared between two groups of patients and healthy groups using a Mann-Whitney test and an unpaired t-test. MiR-21’s median CT value was 29.68 in the OSCC group and 32.89 in the healthy group, and miR-29a’s median CT value was 37.54 and 36.46 in the OSCC group and healthy group, respectively. Additionally, miR-132’s CT values were 37.71 and 36.40, miR-138’s CT value was 35.37 and 31.21, and miR-204’s CT value was 36.44 and 36.17. The results showed that miR-21 expression levels increased significantly, while miR-29a, miR-132, and miR-138 (P < 0.05), and miR-204 expression levels did not differ significantly (P > 0.05). As a result of this study, the expression levels of microRNAs may be considered to diagnose OSCC at an early stage. It is essential to diagnose this disease early to improve treatment and patient health outcomes.